Chemoselective Biohydrogenation of Alkenes in the Presence of Alkynes for the Homologation of 2‐Alkynals/3‐Alkyn‐2‐ones into 4‐Alkynals/Alkynols. Issue 11 (7th May 2019) - Colombo, Danilo; Brenna, Elisabetta; Gatti, Francesco G.; Ghezzi, Maria Chiara; Monti, Daniela; Parmeggiani, Fabio; Tentori, Francesca
Abstract: The chemoselective hydrogenation of alkenes in the presence of alkynes is a very challenging transformation to achieve with traditional chemical methods. The development of an effective procedure to perform this transformation would enrich the tool‐kit available to organic chemists for the development of useful synthetic routes, and the creation of novel structural motifs. The reduction of activated alkene bonds by ene‐reductases (ERs) is completely chemoselective, because of the mechanism of the reaction. Thus, we investigated the use of ERs belonging to the Old Yellow Enzyme family for the reduction of α, β‐unsaturated aldehydes with a conjugated C≡C triple bond at the γ position. This reaction was exploited as the key step for the development of an effective homologation route to convert aryl and alkyl substituted propynals and butynones into 4‐alkynals and 4‐alkynols, avoiding some troublesome or hazardous steps of known synthetic routes. Abstract :